A WINNING STRATEGY ANALYSIS IN THE GAME “RACE TO 20” THROUGH A COMPUTATIONAL THINKING PERSPECTIVE - Ramos de Lima, José Vitor; Sobreira, Péricles de Lima; Bellemain, Franck Gilbert René; de Castro, Airton Temistocles Gonçalves (VIDYA, 2026)
This article aims to analyze the winning strategy of Race to 20 in the light of the Computational Thinking (CT) pillars. This study was developed collaboratively between members of the Atelier Digitas research group at the Federal University of Pernambuco (UFPE, Brazil), and the Department of Engineering and Computer Science at the Université du Québec en Outaouais (UQO, Canada). The methodological approach included the mathematical modeling of the winning strategy based on the Theory of Combinatorial Games, followed by its analysis according to CT pillars: problem formulation, decomposition, abstraction, pattern recognition, algorithm design, and debugging. The results revealed the potential of problem solving through educational games, and the analysis under the CT framework enabled possibilities of investigation for applying Race to 20 in different educational levels (from primary to higher education), especially in the teaching of progressions, patterns, and mathematical induction.